Behavioral Differences in Gaming Patterns among Chinese Subcultures as Perceived by Macao Casino Staff. (November 2013) - Wan, Penny Yim King; Kim, Samuel Seongseop; Elliot, Statia
Given the growth of Macao's casino industry and its popularity with Chinese visitors from various locations, an understanding of subcultural differences is critical. This study reports on the observations of a convenience sample of 302 long-time Macao casino staff members regarding casino customers from Mainland China, Hong Kong, and Taiwan. While these customers have much in common, the employees reported differences in the three subcultures' gambling behavior, in the areas of untidy or disruptive behavior, generous (tipping) behavior, complaining and active behavior, passive behavior, game-focused behavior, and chip-exchange behavior. By understanding and addressing these differences, many of which are relatively subtle, the managers of Macao's casinos can improve the quality of service offered to these guests.